A Silent Threat: A Case Study of Oral Malignant Melanoma - Kukde, Monal M.; Madurwar, Anil U.; Selokar , Deepak; Noman, Obaid (Medical Science: Recent Advances and Applications Vol. 1, 2025)
Melanoma of the oral cavity is a rare malignant tumor that develops from a malignant melanocytic or de novo from melanocytes within the normal mucosa or skin and appears blue, black, or reddish-brown. Oral melanomas develop quietly, with only a few signs, until they have progressed. Oral mucosal melanoma has a higher proclivity for metastasis and attacks tissue more aggressively than any other malignant tumor in the mouth. Intestinal melanoma of the head and neck is an uncommon type of cancer that should be counted among the deadliest. Malignant melanoma of the oral cavity accounts for only 0.2%-8.0% of all reported melanoma, although it accounts for 0.5% of all malignant neoplasia of the oral cavity. Because most melanotic mucosal lesions are painless at first, the diagnosis is sometimes delayed until the ulcer or growth causes symptoms. The prognosis for oral melanoma is poor, with a five-year survival rate of around 10% to 25%. Life expectancy is fewer than two years on average. Early detection is critical for effective therapy and the only way to improve survival and prognosis in patients with oral malignant melanoma due to its poor prognosis. To avoid oral melanomas, every single-colored lesion identified in the oral cavity should be treated with suspicion and adequate inquiry because a colored lesion might expand, and it should be referred for a biopsy to avoid misdiagnosis. A 70-year-old female patient visited the outpatient department with the major complaint of a non-tender growth in the right back area of the maxilla for one month. The patient was known for consuming betel nuts and putting them in the oral cavity and chewing for long hours. A CT scan revealed hypodense soft tissue density that developed into a massive lesion that appeared to cover the upper right alveolar arch. The patient was diagnosed with Malignant melanoma. The patient presented after three months and the size and extent of the lesion had increased. This study shows how the oral clinic is important in the diagnosis of oral ulcers and argues that early detection is necessary to enhance patient outcomes.